THE OCCURRENCE AND ANTIBIOGRAM OF Salmonella gallinarum ISOLATED FROM CLOACAL SWABS OF CHICKENS IN JOS SOUTH LOCAL GOVERNMENT AREA, PLATEAU STATE - Dasat, G. S.; Danjuma, G.; Chuga, A. P. (FUDMA JOURNAL OF SCIENCES, 2020)
Fowl typhoid caused by Salmonella gallinarum are controlled by biosecurity and vaccination by the poultry industry, however, these bacteria are still present in the poultry environment and outbreaks are often reported worldwide. Salmonella enterica serotype Gallinarum (S. gallinarum) is the causative agent of fowl typhoid (FT) in chickens causing heavy economic losses to poultry industry through mortality, reduced egg production and culling of breeding stocks. This study was designed to investigate the prevalence rate of Salmonella gallinarum from chicken cloacal swabs and antibacterial susceptibility in Jos South Local Government Area, using standard bacteriological methods. A prevalence rate of 4 % was obtained out of the 100 samples. Serovar detected was Salmonella gallinarum4 (4 %). Analysis of antibacterial susceptibility shows all isolates were 100 % sensitive to Ciprofloxacin and Gentamycin and 100 % resistant to Oxytetracycline, Erythromycin and Ampicillin. Fifty percent sensitive to Ceftriaxone while 1 (25 %) of the isolates were sensitive to Streptomycin and Amoxicillin-Clavulanic acid. Conclusively, this result indicates that Salmonella gallinarum can be isolated in cloacal swabs of asymptomatic broiler and layer chickens in the poultry farms. The use of drugs for prophylaxis and therapeutic purposes can be regulated and monitored to avoid transfer of resistant genes to human and other animals